Serum Bilirubin Levels and Extent of Symptomatic Intracranial Atherosclerotic Stenosis in Acute Ischemic Stroke: A Cross-Sectional Study - Yu, Fang; Zhang, Lin; Liao, Di; Luo, Yunfang; Feng, Xianjing; Liu, Zeyu; Xia, Jian (Frontiers in Neurology, 2021)
Abstract Background: Bilirubin plays a paradoxical role in the pathological mechanism of stroke. To date, few clinical studies have investigated the effect of serum bilirubin on symptomatic intracranial atherosclerotic stenosis (sICAS). This study aims to evaluate the connection between serum bilirubin and sICAS. Methods: From September 2015 to May 2020, 1156 sICAS patients without hepatobiliary diseases admitted to our hospital were included. Patients were distributed into none-mild (0-49%), moderate (50-69%) and severe-occlusion sICAS groups (70-100%) by the degree of artery stenosis. Moderate and severe-occlusion sICAS patients were classified into three groups by the number of stenotic arteries (single-, two- and multiple-vessel stenosis). The relationship between serum bilirubin levels and sICAS was analyzed by logistic regression analysis. Results: In univariable analyses, sICAS patients with severe and multiple atherosclerotic stenoses had lower levels of total bilirubin (Tbil), direct bilirubin (Dbil), and indirect bilirubin (Ibil). In multinomial logistic regression analyses, when compared with the highest tertile of bilirubin, lower levels of Tbil, Dbil, and Ibil showed higher risks of severe-occlusion sICAS (95% CI: 2.018-6.075 in tertile 1 for Tbil; 2.380-7.410 in tertile 1 for Dbil; 1.758-5.641 in tertile 1 for Ibil). Moreover, the logistic regression analyses showed that lower levels of Tbil, Dbil, and Ibil were related to multiple (≥3) atherosclerotic stenoses (95% CI: 2.365-5.298 in tertile 1 and 2.312-5.208 in tertile 2 for Tbil; 1.743-3.835 in tertile 1 and 1.416-3.144 in tertile 2 for Dbil; 2.361-5.345 in tertile 1 and 1.604-3.545 in tertile 2 for Ibil) when compared with tertile 3. Conclusions: Lower bilirubin levels might be the indicators of severe and multiple atherosclerotic stenoses of patients with sICAS.